Commenting as a genre. Tehilim. (2020). Tehilim - Psalms. Commentary by Rabbi Shimshon Raphael Hirsch (Vol. 1-2). Kyiv: Duh i Litera. - Kuznetsov, Vsevolod (Sententiae, 2022)
Review of Tehilim. (2020). Tehilim - Psalms. Commentary by Rabbi Shimshon Raphael Hirsch (Vol. 1-2). Kyiv: Duh i Litera.